High cycle fatigue behavior of hard turned 300 M ultra-high strength steel. (February 2020) - Ajaja, J.; Jomaa, W.; Bocher, P.; Chromik, R.R.; Brochu, M.
Graphical abstract: Abstract: Although the effects of hard turning on surface integrity have been extensively studied over the past decades, the fatigue behavior of hard turned ultra-high strength steels is still not completely understood. This study investigated the influence of surface integrity characteristics generated by hard turning on the rotating bending fatigue life of 55 HRC 300 M steel. Four finish cutting conditions were used to generate different combinations of surface integrity characteristics. Resulting fatigue lives ranged between 1.01∙10 5 and 9.84∙10 6 cycles for a stress amplitude of 965 MPa. A single distribution was able to fit the entire fatigue life data showing that the finish hard turning conditions evaluated are comparable. A fractographic analysis showed that specimens failed under two different crack initiation mechanisms: surface feed marks and subsurface Al2 O3 ∙CaO∙MgO inclusions. Murakami's K max equation for surface defects underestimates the severity of machined surfaces and cannot explain the competition between the two crack initiation mechanisms.